Kidney transplantation in systemic sclerosis: Advances in graft, disease, and patient outcome - Maritati, Federica; Provenzano, Michele; Lerario, Sarah; Corradetti, Valeria; Bini, Claudia; Busutti, Marco; Grandinetti, Valeria; Cuna, Vania; La Manna, Gaetano; Comai, Giorgia (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is an immune-mediated rheumatic disease characterized by vascular abnormalities, tissue fibrosis and inflammation. Renal disease occurring in patients with SSc may have a variable clinicopathological picture. However, the most specific renal condition associated with this disease is the scleroderma renal crisis (SRC), characterized by acute onset of renal failure and severe hypertension. SRC develops in about 20% of cases of SSc, especially in those patients with diffuse cutaneous disease. The prognosis of this condition is often negative, with a rapid progression to end-stage renal disease (ESRD). The advent of the antihypertensive angiotensin converting enzyme inhibitors in 1980 was associated with a significant improvement in patient’s survival and recovery of renal function. However, the prognosis of these patients can still be improved. The dialytic condition is associated with early death and mortality is significantly higher than patients undergoing renal replacement therapy (RRT) due to other conditions. Patients with SRC who show no signs of renal functional recovery despite timely blood pressure control are candidates for kidney transplant (KT). In this review, we reported the most recent advances in KT in patients with ESRD due to SSc, with a particular overview on the risk of disease recurrence after transplantation and the evolution of other disease manifestations.